Thinking Systematically About Scaling Up : Developing Guidance for Scaling Up World Bank-Supported Agriculture and Rural Development Operations - Jonasova, Marketa; Cooke, Sanjiva (World Bank, Washington, DC, 2017)
The objective of this report is to assess the usefulness of providing guidance for scaling up good practices in core ARD business lines, and to test the prospects for doing so. The output of the document is a guide for a systematic discussion on scaling up of Competitive Grant Schemes (CGSs) for agricultural research and extension at key decision points during the life of an ARD project. This report addresses the other end of the state-of-practice spectrum - good practices and beyond. The preparation of this report entailed five main activities: An overview of scaling up concepts and approaches; the selection of a particular sub-area within one of ARD s core business lines - scaling up CGS for agricultural research and extension; application of the IFAD/Brookings framing questions to five World Bank projects that were identified as addressing that business line - using information provided by the project's task team leaders (TTLs) or other member of the project team; the development of sub-area specific guidance for a systematic discussion on scaling up based on the findings from a series of five case studies; and validation of the scaling up guidance for CGSs for agricultural research and extension by World Bank practitioners and other internal consultations.